Safety sans Frontières: An International Safety Culture Model. Issue 5 (13th February 2015) - Reader, Tom W.; Noort, Mark C.; Shorrock, Steven; Kirwan, Barry
<x xml:space="preserve">Abstract</x> The management of safety culture in international and culturally diverse organizations is a concern for many high‐risk industries. Yet, research has primarily developed models of safety culture within Western countries, and there is a need to extend investigations of safety culture to global environments. We examined (i) whether safety culture can be reliably measured within a single industry operating across different cultural environments, and (ii) if there is an association between safety culture and national culture. The psychometric properties of a safety culture model developed for the air traffic management (ATM) industry were examined in 17 European countries from four culturally distinct regions of Europe (North, East, South, West). Participants were ATM operational staff (n = 5, 176) and management staff (n = 1, 230). Through employing multigroup confirmatory factor analysis, good psychometric properties of the model were established. This demonstrates, for the first time, that when safety culture models are tailored to a specific industry, they can operate consistently across national boundaries and occupational groups. Additionally, safety culture scores at both regional and national levels were associated with country‐level data on Hofstede's five national culture dimensions (collectivism, power distance, uncertainty avoidance, masculinity, and long‐term orientation). MANOVAs indicated safety culture to be most positive in Northern Europe, less so in Western and Eastern Europe, and least positive in Southern Europe. This indicates that national cultural traits may influence the development of organizational safety culture, with significant implications for safety culture theory and practice.